Sleep Apnea and the Cerebrovascular Disease Correlation - Hoyle, Brian (MD Conference Express, 2014)
This article gives an overview of obstructive sleep apnea (OSA) as a risk factor for cerebrovascular disease and stroke [Culebras A, editor. Sleep, Stroke and Cardiovascular Disease. Cambridge University Press, 2013].